Stair climbing robot - Sharifah Fatma Munirah, Syed Zain (2017)
Robots are generally required to help our everyday schedules particularly for tasks that are difficult to be done by us. The primary focus of the proposed project is to carry the load of 50 kg upwards the stairs. Then, the suitable of the microcontroller and the sensor of the robot is chosen to achieve the main objectives to be able the robot to carry the load on the stair. This project is divided into two sections which are software and hardware. There are two types of software that used in this project which is PROTEUS and Arduino. This software is using output and input to declare which pin low or high. This software can give command at pin input and output. We just select the pin that we want to the input and output. The hardware components that connect to the microcontroller are DC gear motor, gyro sensor MPU6050 and other components. It controls all the functions of the robot especially to control the motor speed during the robot is move. As the result from the purposed project, we had expected to build a very useful robot that is capable to carry 50kg load on rough surfaces and upwards and downwards stairs. We can conclude that with the help of the stair climbing robot, many people can use the robot to carry a heavy load upwards and downwards stairs. A more convenient and harmonic life can be achieved by using the stair climbing robot.